Evidence of Pore‐ and Fracture‐Filling Gas Hydrates from Geophysical Logs in Consolidated Rocks of the Muli Area, Qinghai–Tibetan Plateau Permafrost, China. Issue 7 (24th July 2019) - Peng, C.; Zou, C. C.; Lu, Z. Q.; Yu, C.Q.; Liu, A. Q.; Tang, Y. Y.; Hu, X. D.; Zhang, S. X.; Wen, H. J.; Li, Y. H.; Wang, W. C.
Abstract: Natural gas hydrates were discovered in the Muli area of the Qinghai–Tibetan Plateau permafrost, which is an area of alpine permafrost in the midlatitudes. Resistivity models were employed to understand the distribution and accumulation mechanism of gas hydrates in the Muli area, as these models are suitable for use in detecting the presence and amount of pore‐ and fracture‐filling gas hydrates in consolidated rocks, and geophysical logs were used to constrain gas hydrate saturation. The results show that resistivity logs are sensitive to gas hydrate saturation in consolidated rocks in the Muli area. Geophysical log analysis enabled the discovery of eleven pore‐filling gas hydrate reservoirs (total thickness: 21.95 m) and nine fracture‐filling gas hydrate reservoirs (total thickness: 90.55 m). It is hypothesized that gas accumulation is more likely to occur in fractures within mudstones due to good permeability and sealing properties and that fracture‐filling gas hydrates are more likely to occur than pore‐filling gas hydrates. Poor preservation conditions may thus be the key factor in the absence of gas hydrates in the eastern part of the study area. Evidence from geophysical logs shows that the upper boundary of the gas hydrate stability zone in the Muli area is at a depth of 133.25 m and that the lower boundary is deeper than 400 m. The results of this study are useful for further gas hydrate exploration in alpine permafrost at the midlatitudes. Key Points: Resistivity logs are more sensitive to gas hydrate saturation than compressional‐wave velocity logs in consolidated rocks of the Muli area Resistivity models of pore‐ and fracture‐filling gas hydrate reservoirs are used to detect gas hydrates in consolidated rocks Gas hydrate accumulation in the Muli area is affected by faults, lithology, and the gas hydrate stability zone